2010
DOI: 10.1308/rcsann.2010.92.8.660
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of on-site cytology with ultrasound-guided fine needle aspiration in a one-stop neck lump clinic

Abstract: This audit has illustrated the benefits of a one-stop clinic with on-site cytology in providing a rapid diagnostic head and neck cancer service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Of those cases with histological correlates, agreement with FNA results was 94% for cytopathologists and 67% for clinicians. 5 Our study does not consider the level of confidence of the cytotechnician in the adequacy of the FNA specimen submitted for processing as it is possible the specimens could not be bettered by the surgeon despite repeated attempts. This information was not recorded in the clinical notes and therefore could not be considered.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Of those cases with histological correlates, agreement with FNA results was 94% for cytopathologists and 67% for clinicians. 5 Our study does not consider the level of confidence of the cytotechnician in the adequacy of the FNA specimen submitted for processing as it is possible the specimens could not be bettered by the surgeon despite repeated attempts. This information was not recorded in the clinical notes and therefore could not be considered.…”
Section: Discussionmentioning
confidence: 94%
“…5 They found that the absence of on-site cytological evaluation would have resulted in sample inadequacy in 15% of cases (41 of 274 cases), compared with 4% with on-site cytology (11 of 274 cases). In this series, on-site cytopathologist evaluation equated to an 11% risk reduction in the chances of an inadequate sample, which is comparable with the findings of our study with on-site cytotechnician assessment.…”
Section: Discussionmentioning
confidence: 99%
“…7 A cytologist is reported to cost £81 per hour. 8 The potential financial savings associated with the detection and immediate repetition of non-diagnostic FNAs, over 6 months, would therefore be: (28 × £63) + (28 × £66) + (7 × £81) = £1764 + £1848 + £567 = £4179. The cost of employing a cytology technician to assess FNA adequacy is reported to be £20 per hour.…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…The cost of employing a cytology technician to assess FNA adequacy is reported to be £20 per hour. 8 With 21 clinics over the 6 month period, each lasting 3 hours, the cost of onsite cytology assessment would be: 21 × 3 × £20 = £1260. In theory, the net saving associated with onsite cytology assessment of neck lump FNAs by a cytology technician is £4179 − £1260 = £2919 over 6 months, or £5838 per annum.…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…The advantages of ultrasound-guided FNAC coupled with onsite cytology in a one-stop neck mass clinic which allows immediate assessment of the aspirate and repeated passage, if necessary, are well recognized and reduced the inadequacy rate from 15 to 4% in a recent study of 274 patients [36]. Even in difficult areas like thyroid pathology, on-site cytology with routine second opinion review of indeterminate biopsies can be helpful and potentially obviate the need for diagnostic thyroidectomy in 25% of patients without increasing the false-negative rate [36].…”
Section: Categorization Of Diagnostic Discrepanciesmentioning
confidence: 99%